Dispersed craft production systems at Rooiberg, c. 1200–1850, and broader implications for southern African history - Chirikure, Shadreck; Bandama, Foreman; Hall, Simon; Killick, David; Mathoho, Ndivhuwo Eric; Nkhasi-Leosana, Mamakomoreng; Rosenstein, Dana Drake; Thondhlana, Thomas (Southern African Humanities, 2023)
Recent literature is slowly stepping back from the idea that regions located away from centres of powerful social formations (such as chiefdoms, states and empires) lacked agency and initiative. We contribute to this conversation by engaging with the Rooiberg craft production landscape. We argue that Rooiberg was an ‘open source’ that was owned by no one, and provide some examples of ‘open sources’ elsewhere. Concerning the organisation of production, Rooiberg metalworking was more dispersed than concentrated. No centralised polity directly controlled the distribution of tin or other metals extracted from this resource-rich region. Consequently, different communities producing crafts at Rooiberg controlled their destiny and traded and exchanged with others through intricate capillary circulatory systems. The frequency of objects recovered from excavations indicates that these systems involved mostly internal commodities, with limited amounts of exotica from the Indian Ocean trade.